A Potent and Protective Human Neutralizing Antibody Against SARS-CoV-2 Variants - Shan, Sisi; Mok, Chee Keng; Zhang, Shuyuan; Lan, Jun; Li, Jizhou; Yang, Ziqing; Wang, Ruoke; Cheng, Lin; Fang, Mengqi; Aw, Zhen Qin; Yu, Jinfang; Zhang, Qi; et al. (Frontiers in Immunology, 2021)
As severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants continue to emerge and spread around the world, antibodies and vaccines to confer broad and potent neutralizing activity are urgently needed. Through the isolation and characterization of monoclonal antibodies (mAbs) from individuals infected with SARS-CoV-2, we identified one antibody, P36-5D2, capable of neutralizing the major SARS-CoV-2 variants of concern. Crystal and electron cryo-microscopy (cryo-EM) structure analyses revealed that P36-5D2 targeted to a conserved epitope on the receptor-binding domain of the spike protein, withstanding the three key mutations—K417N, E484K, and N501Y—found in the variants that are responsible for escape from many potent neutralizing mAbs, including some already approved for emergency use authorization (EUA). A single intraperitoneal (IP) injection of P36-5D2 as a prophylactic treatment completely protected animals from challenge of infectious SARS-CoV-2 Alpha and Beta. Treated animals manifested normal body weight and were devoid of infection-associated death up to 14 days. A substantial decrease of the infectious virus in the lungs and brain, as well as reduced lung pathology, was found in these animals compared to the controls. Thus, P36-5D2 represents a new and desirable human antibody against the current and emerging SARS-CoV-2 variants.